Simulation Strategy and Oral Skill: A Classroom Action Research at SMPN 1 Citeureup - Nuarsih, Rosinta Uli (JET (Journal of English Teaching), 2018)
This article reports how simulation strategy applied to improve student’s speaking skill. The participants were 36 students of State Junior High School 1Citeureup, Kranggan, West Java. For about two months they were taught speaking using simulationstrategy. The instruments used were speaking test and observation. The data were analyzed using the descriptive analysis technique. It was found that there were improved teaching and learning atmosphere and increased students’ oral performance. The students’ speaking ability improvement is evidenced by the mean score of students' pretest performance, 44.00, becoming 51.33 (or 17% got improved) in the first cycle and 84.33 (or 92% got improved) in the second cycle. It also revealed that the total percentage improvement of the students’ speaking skill was 92%.